A Correlative Study on EFL Students’ Binge Watching Behaviors and Their Vocabulary Mastery - Burhanuddin Burhanuddin; Rosmiaty Rosmiaty; Nurul Fadilah (Universitas Negeri Makassar, 2020)
In this study, the writer aims to know the correlation between students habits in watching english movie and their vocabulary mastery of The Fourth Semester Students in ABA-UMI 2017. The whole population of this study was The Fourth Semester Students of ABA-UMI. The sample was 20 students, the sample is taken by using purposive sampling technique.Based on the analysis of Data, the students habit in watching English movies, 3 students are in bad category (15%), 10 students are in fair category (50%), 7 students are in good category (35%), and no students are in very strong category. The vocabulary mastery, there are no students who got score less than 50 (poor category). Furthermore, there are 2 students (10%) who got score between 50 and 59 (low category); 2 students (10%) who got score between 60 and 69 (fair category); 10 students (50% ) who got score between 70 and 79 (good category); and 6 students (30%) who got score between 80 and 100 (excellent category).The result revealed that there is correlation between students habit in watching English movies and students’ vocabulary mastery. It is suggested that (1) The use of media cannot be separated from teaching and learning process. The use of movie is very helpful in learning process because it can makes more interested to the material and make students learn happily. (2) Hopes that students can improve their English ability independently. For example; by using media to improve their English.